Hipoalbuminemia: Patofisiologi dan Tata Laksana: Tinjauan Pustaka - Angelia, Cynthia Lady (PT Kalbe Farma Tbk., 2025)
Hypoalbuminemia is a condition of low blood albumin concentration (<3.5 g/dL). Hypoalbuminemia reflects more on the level of physiological stress caused by one or more diseases than lack of nutrition. Hypoalbuminemia is found mostly in inpatient, critically-ill, and geriatric patients. Hypoalbuminemia causes poor functional state, longer hospitalization, and higher morbidity and mortality. The three most common causes of hypoalbuminemia are: (1) Decreased production of albumin, (2) Increased loss of albumin via the kidneys, gastrointestinal tract, skin, or extravascular space, and (3) Increased catabolism of albumin. Management of hypoalbuminemia is to find the underlying disease, and oral or parenteral supplementation of albumin. Parenteral albumin administration is recommended in specific conditions, such as patients with cirrhosis undergoing large-volume paracentesis (ascites >5 liters), hepatorenal syndrome, spontaneous bacterial peritonitis, and burns involving more than 30% of total body surface area after the first 24 hours. In patients with sepsis, acute respiratory failure, major non-cardiac surgery, or cardiac surgery, parenteral albumin may be considered when hemodynamic stability cannot be achieved with crystalloids. Conversely, parenteral albumin administration is not recommended as maintenance fluid or initial resuscitation in patients with acute traumatic brain injury.